Electric power generating bicycle - Brito, Nuno (2006)
It is manifest the growing interest in both personal health and environmental issues. The device described on this paper contemplates both aspects: generating environment-friendly electric power while keeping fit. A car alternator excited through a 12V battery is coupled to a mountain bicycle, and this arrangement enables the lighting of six halogen lamps, if a cyclist pedals fast enough. Such a machine gives rise to the thought of a self-powered gymnasium. Considerable physical effort is required in order to make the lamps glow, which is pedagogical since it shows clearly that spending energy is much easier than generating it.